Emerging roles of long noncoding RNAs in neurological diseases and metabolic disorders - Yingqun Huang (Frontiers Research Topics, 2015)
Long noncoding RNAs (lncRNAs) are a new class of transcripts that are in general longer than 200 nucleotides and that have no protein-coding potential. The vast majority of vertebrate genomes encode diverse and complex lncRNAs that play regulatory roles at almost every step of gene expression. Recently, increasing evidence has implicated lncRNAs in the pathogenesis of various human diseases. The purpose of the Research Topic, "Emerging roles of long noncoding RNAs in neurological diseases and metabolic disorders", is to bring together leading researchers in the field who, through contributing to an organized and comprehensive collection of peer-reviewed articles, provide a broad perspective on the latest advances in the field. A number of interesting and cutting-edge areas will be covered as below, but this list is not exclusive: - The methodologies and technologies of identifying and studying lncRNAs - LncRNAs in gene-specific transcription - LncRNAs in epigenetic regulation - LncRNAs in post-transcriptional regulation - LncRNAs in disease - Mapping of noncoding single nucleotide polymorphisms associated with disease.